Designer liquid-liquid interfaces made from transient double emulsions. Issue 1 (December 2018) - Dockx, Greet; Geisel, Steffen; Moore, David; Koos, Erin; Studart, Andre; Vermant, Jan
Abstract Current methods for generating liquid-liquid interfaces with either controlled composition or coverage often rely on adsorption equilibria which limits the freedom to design such multiphase materials, in particular when different components are used. Moreover, when interfaces become densely populated, slowing down of adsorption may impose additional constraints. Up to now, it is not possible to control surface coverage and composition of droplet interfaces at will. Here, we report a generic and versatile method to create designer liquid-liquid interfaces, using transient double emulsions. We demonstrate how the surface coverage in Pickering emulsions can be controlled at will, even for dense particulate layers going up to multilayers. Moreover, composite droplet interfaces with compositional control can be generated, even with particles which would have intrinsically different or even opposite adsorption characteristics. Given its simplicity, this method offers a general approach for control of composition of liquid-liquid interfaces in a variety of multiphase systems. Surfaces with adsorbed and arrested colloids are of interest for the engineering of advanced mesostructured materials. Here the authors demonstrate a method for producing particle-stabilised droplets with controlled surface coverage and composition.